(untitled) (Docentes 2.0 Journal, 2023)
Public sector procurement represents a significant part of the budgets of most countries; and, sometimes, these procedures are permeated by practices that raise concerns regarding the integrity and transparency of these processes, which has an adverse impact on the quality of life of citizens, by diverting resources that were intended for the progress and development of the country. The purpose of this research was to analyze the control in public procurement. The research was based on the inductive method, positivist paradigm, with qualitative approach, non-experimental design, descriptive type. A bibliographic review of scientific productions of national and international indexing journals was carried out and the documentary analysis guide was used as an instrument. The review identified that about 30% of institutions use environmental processes, risk, information systems and control and monitoring activities to efficiently manage public resources. The study highlights the relevance of control in public procurement as a fundamental component for a more efficient management of public resources.